(untitled) (Papeles, 2022)
The article addresses the questioning about the application of the exclusion of companies of cultural interest from the business rescue established by art. 48 LCQ. The validity and rationality of the measure is questioned, concluding its repeal. The possible hypotheses are also analyzed before their validity, concluding for that scenario their non-application.